Association of Patient-Reported Narcotic Use With Short- and Long-Term Outcomes After Adult Spinal Deformity Surgery: Multicenter Study of 425 Patients With 2-year Follow-up. Issue 19 (1st October 2018) - Raad, Micheal; Jain, Amit; Neuman, Brian J.; Hassanzadeh, Hamid; Gupta, Munish C.; Burton, Douglas C.; Mundis, Gregory M.; Lafage, Virginie; Klineberg, Eric O.; Hostin, Richard A.; Ames, Christopher P.; Bess, Shay; et al.
Abstract : Study Design: Retrospective analysis of a prospective registry Objective: To investigate associations of preoperative narcotic use with outcomes after adult spinal deformity (ASD) surgery. Summary of Background Data: We hypothesized that preoperative narcotic use would predict longer hospital stays, greater postoperative narcotic use, and greater disability 2 years after ASD surgery. Methods: A multicenter database of surgical ASD patients was analyzed retrospectively for patients with self-reported data on preoperative narcotic use. Patients were categorized as using narcotics daily or non-daily (including those who used no narcotics), according to self-report. Outcomes were prolonged length of hospital stay (LOS) (>7 days); length of intensive care unit (ICU) stay; and daily narcotic use and Oswestry Disability Index (ODI) scores 2 years postoperatively. Groups were compared by demographic characteristics, pain, disability, radiographic deformity, and surgical invasiveness. Multivariate logistic and linear regression were used to determine associations between preoperative narcotic use and outcomes. Results: Of 575 patients who met the inclusion criteria, 425 (74%) had complete 2-year follow-up data. Forty-four percent reported daily preoperative narcotic use. Compared with non-daily users, daily narcotic users were older, had more comorbidities, more severe back pain, higher ODI scores, longer operative times, and worse preoperative malalignment and were more likely to undergo 3-column osteotomy (all, P  < 0.05). Daily narcotic use independently predicted prolonged LOS (odds ratio [OR] = 1.7, 95% confidence interval [CI] = 1.1–2.9), longer ICU stay (difference = 16 hours, 95% CI = 1.9–30 hours), and daily narcotic use 2 years postoperatively (OR = 6.9, 95% CI = 3.7–13), as well as worse 2-year ODI score (difference = 4.5, 95% CI: 0.7–8.3, P  = 0.021). Conclusion: Daily narcotic use before ASD surgery was associated with prolonged LOS, longer ICU stays, and increased risk of daily narcotic use and greater disability 2 years postoperatively. Level of Evidence: 3